Pengaruh Penerbitan Sukuk Ijarah Terhadap Return On Assets, Return On Equity dan Earning Per Share Emiten di Bursa Efek Indonesia Tahun 2009-2013 - Rianda Ajeng Ardiyanti Putri; Leo Herlambang (Universitas Airlangga, 2015)
Sukuk in Indonesia is growing rapidly with marked Corporate Sukuk issuance reached 65 Sukuk. Within this development also trigger the issuance of Ijarah Sukuk more in demand by the issuer as it is considered more prospective than the Mudharabah Sukuk.This study aimed to determine the issuance effect of Ijarah Sukuk on the financial performance issuer in the Indonesia Stock Exchange in 2009 to 2013. The independent variable in this study is Sukuk to Equity Ratio and the dependent variable in this study are Return on Assets, Return on Equity and Earnings per Share. The analysis technique used is a simple linear regression analysis OLS with 95% of confidence level.The results of this study show that Sukuk to Equity Ratio has significant effect on Return on Assets, but Sukuk to Equity Ratio has not significant effect on Return on Equity and Earnings per Share.